Pengaruh Tahapan Melipat Media Kertas Buffalo terhadap Kemampuan Motorik Halus Anak Usia 4-5 Tahun di TK Ihyaul Ulum Lamongan - Dwi saadah (Sekolah Tinggi Ilmu Tarbiyah Muhammdiyah Muhammadiyah Bojonegoro, 2025)
This Pre-Experimental design research with one group pretest posttest type aims to determine the effect of the stages of folding buffalo paper media on the fine motor skills of children aged 4-5 years at Ihyaul Ulum Kindergarten. The subjects in this research were group A children at Ihyaul Ulum Lamongan Kindergarten, totaling 18 children. The data collection techniques used are observation and documentation. The data analysis technique uses the Wilcoxon Matched Pairs Test. Based on the results of data analysis, it was obtained that Tcount=0 and Ttable for N=18 with a significance level of 5% of 40, so (0<40). The data shows that H0 is rejected and Ha is accepted. The results of research on the influence of the stages of folding buffalo hard media on the fine motor skills of children aged 4-5 years at Ihyaul Ulum Lamongan Kindergarten are influential. This is because the folding activity is carried out according to the stages. Apart from that, buffalo paper is paper that has a smooth, smooth texture and looks like wood grains and has many color choices and is quite thick. So it can be concluded that the stages of folding buffalo paper influence the fine motor skills of children aged 4-5 years at Ihyaul Ulum Lamongan Kindergarten.